Letter to the Editor and response: Was the egg a plausible source for the Salmonella Potsdam outbreak? - Arzey, George; Unicomb, Leanne E; Bird, Phillip; Dalton, Craig (Communicable Diseases Intelligence, 2004)
This report published in Communicable Diseases Intelligence, Volume 28, Number 2 contains a Letter to the Editor questioning some aspects of a previously published article on an outbreak of Salmonella Potsdam associated with salad dressing at a restaurant. Includes responses.